Application of cow manure and Gliricidia sepium pruning compost to improve physical properties of Ultisols and soybean yield - Zurhalena Zurhalena; Endriani Endriani; Yulfita Farni; Najla Anwar Fuadi (Journal of Degraded and Mining Lands Management, 2023)
Ultisols have considerable potential in developing agricultural cultivation, but in their management, they face several obstacles, including physical properties that do not adequately support plant growth. The low content of soil organic matter causes poor soil physical properties. Low organic matter content leads to low soil aggregate stability, obstructing pore distribution and infiltration so the soil can easily become compacted. This study aimed to observe the changes in some physical properties of the soil due to the application of cow manure and Gliricidia sepium pruning compost and its effect on the yield of soybean plants. This study used a randomized block design with five treatments, namely, K0 (without cow manure-Gliricidia compost), K1 (5 t ha-1cow manure-Gliricidia compost), K2 (10 t ha-1cow manure-Gliricidia compost), K3 (15 t ha-1cow manure-Gliricidia compost), and K4 (20 t ha-1cow manure-Gliricidia compost). The results showed that the 15 t ha-1 cow manure-Gliricidia compost was the best dose in improving the total pore space and penetration resistance of the soil studied. The application of 15 t ha-1cow manure-Gliricidia compost significantly increased soybean yield, reaching 2.97 t ha-1.